SIMULATION OF CHARACTERISTICS OF DUAL-CORE PHASE SHIFTING TRANSFORMER - Kalinin L.P.; Golub I.V.; Zaitsev D.A.; Tirsu M. (Problems of the Regional Energetics, 2014)
The role and importance of phase shifting transformers are increased as a result of the further development of integrated power systems. This gives the rise to new technical solutions which entails the necessity of comparison of new developments with existing. The article consider the technical characteristics of dual-core phase shifting transformer which later will be used as a basis for comparison with other competing options and assess of their technical efficiency.